2022
DOI: 10.3390/ph15060683
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose—Adaptation of a Nature-Identical Material to the Needs of Advanced Chronic Wound Care

Abstract: Modern wound treatment calls for hydroactive dressings. Among the variety of materials that have entered the field of wound care in recent years, the carbohydrate polymer bacterial cellulose (BC) represents one of the most promising candidates as the biomaterial features a high moisture-loading and donation capacity, mechanical stability, moldability, and breathability. Although BC has already gained increasing relevance in the treatment of burn wounds, its potential and clinical performance for “chronic wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
0
6
0
5
Order By: Relevance
“…To simulate the fluid-releasing capabilities of the loaded BNC more closely to the physiological situation, the amount of liquid delivered from the BNC fleece to a gelatin gel [ 42 ] was determined ( Figure 5 b). Qualitatively, as shown in Figure S3 , all gels were visibly swollen at the contact surface to all BNC samples after 48 h incubation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate the fluid-releasing capabilities of the loaded BNC more closely to the physiological situation, the amount of liquid delivered from the BNC fleece to a gelatin gel [ 42 ] was determined ( Figure 5 b). Qualitatively, as shown in Figure S3 , all gels were visibly swollen at the contact surface to all BNC samples after 48 h incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Native and PLGA-loaded BNC were investigated for their fluid-releasing capabilities using a method previously reported by Zahel et al [ 42 ]. Briefly, an aqueous solution containing 142 mmol L −1 sodium chloride as well as 2.5 mmol L −1 calcium chloride (both Carl Roth) was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…In the past five years, there have been many interesting, detailed reviews describing BC production, properties, and applications [43,65,68,[71][72][73][74]76,[166][167][168][169][170][171][172][173][174][175][176][177][178][179]. BC has great potential to be used in medicine [2,3,43,[71][72][73][74][166][167][168][169][170][171][172]179] as a biomaterial for wound dressing [180][181][182][183][184][185][186], tissue engineering [187][188][189][190][191]…”
Section: Gel Film After Purification (E) Afm (Atomic Force Microscopy...mentioning
confidence: 99%
“…In this respect, not only the high biocompatibility, mechanical stability and gas permeability are of particular advantage [ 23 , 24 ]. Clinical data have shown that wound dressings based on BC are able to relieve pain, promote re-epithelization and absorb wound exudate while providing a moist wound milieu [ 25 ]. In particular, the removal of plaque and fibrous tissue via autolytic debridement is significantly enhanced by the moisture donated from BC-based wound dressings and enables successful wound bed preparation [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data have shown that wound dressings based on BC are able to relieve pain, promote re-epithelization and absorb wound exudate while providing a moist wound milieu [ 25 ]. In particular, the removal of plaque and fibrous tissue via autolytic debridement is significantly enhanced by the moisture donated from BC-based wound dressings and enables successful wound bed preparation [ 25 , 26 , 27 ]. Furthermore, the large surface area and water-holding capacity enable the uptake and release of active compounds, even with the possibility of controlling release kinetics [ 23 , 28 ].…”
Section: Introductionmentioning
confidence: 99%